From likes to loyalty: a netnographic study on trust-building in influencer-audience interactions on social media - Fabeil, Noor Fzlinda; Usman, Zaiton; Wijaya, Riesanti Edie; Mauliyah, Nur Ika; Harkaneri; Siddiqui, Bushra (Global Advances in Business Studies, 2025)
This study explores the key themes of trust-building in influencer-audience interactions on social media using a netnographic study. Living netnography explores trust-building, not just based on the actual posting in the social media, but through spiritual paradigm, that might construct the reality and values of trust. The analysis draws on three weeks of observational data from Instagram, YouTube, Twitter, and TikTok, focusing on three influencers from different cultural and regional backgrounds. By lurking at the audiences’ comments and emojis on the influencer’s posting, this study provides five clusters of trust-building based on relevant codes emerged from the data. The findings suggest authenticity, emotional engagement, responsiveness, economic inclusivity and religiosity have explained the meaning of trust. By integrating theoretical and practical insights, the study provides a schematic framework for fostering trust in influencer marketing, highlighting the importance of cultural values in digital environment from the non-Western context perspective.